Estudo comparativo entre silagem de milho e cana taquara na alimentação suplementar de vacas leiteiras - Jardim, W. R.; Peixoto, A. Mendes; Silveira Filho, S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1950)
The A. A. compare corn silage (Zea mays L.) with sugar cane (Saccharum sinensis Roxb.) in the supplementary feeding of dairy cow. Both the feeds were studied in relation to the following points: composition and nutritive value; influence of milk production, milk fat, milk acidity and body weight; cost of production. Both corn silage and sugar cane were analysed by ordinary methods, and their digestibility was determined by means of digestibility coefficients; their composition and nutritive value are, practically, equivalent, but silage showed slight superiority. The feeding experiment was carried out with two groups of six Holstein Friesian cows each, of the Escola Superior de Agricultura "Luiz de Queiroz" herd. Both groups were fed with the same basic concentrates mixture, calculeted according to MORRISON. During the various periods of the experiment, only the roughage supplement varied. The supplementary feeding consisted of 15 kg of chopped sugar cane or corn, silage, per day and per cow, given in two daily meals in the barn. At 4,30 p.m., the cows are set free in the field, where they pass the over night. The experiment was divided into six periods, in which there was a gradative change of the supplementary feeding between the two groups. The milk was weighed every day; the analysis of milk fat and acidity and the weighing of the animals, were made only on the first three days of every week. The analysis of data showed that: a) Milk production was increased significantly by silage feeding; b) The ri was not any influence on milk fat; c) The silage caused higher milk acidity; d) The sugar cane gave a greater increase of body weight. The cost of production of corn silage was 2,12 time higher, than sugar cane, hence, although the silage gave a higher milk production, its use is not economical, compared with sugar cane, in our conditions.